Autonomous operation of 3D DNA walkers in living cells for microRNA imaging. Issue 3 (13th January 2021) - Hu, Hui; Zhou, Fu; Wang, Baojuan; Chang, Xin; Dai, Tianyue; Tian, Ruifen; Wan, Yifei; Wang, Xiayan; Wang, Guangfeng
Abstract : Three dimensional (3D) DNA walkers hold great potential in serving as an ideal candidate for signal transduction and amplification in bio-assays. Abstract : Three dimensional (3D) DNA walkers hold great potential in serving as an ideal candidate for signal transduction and amplification in bio-assays. However, the autonomous operation of 3D DNA walkers inside living cells is still few and far between, which could be attributed to the lack of suitable driving forces and moderate efficiency in terms of the cellular uptake of such complex 3D DNA components. Herein, a newly updated autonomously operated and highly integrated 3D DNA walker on Au nanoparticles (Au NPs)/zeolitic imidazolate framework-8 (ZIF-8) was activated in a tumor microenviroment and its signal amplified assay capability in living cells was demonstrated using miRNA as a sensing model biomolecule. Specifically, we assembled a 3D DNA motor, including Zn 2+ -dependent DNAzyme and substrates on the AuNPs grafted on ZIF-8. After being delivered into a living cell, ZIF-8 was efficiently degraded in the tumor microenvironment (low pH value), locally releasing the Zn 2+ and DNA motor. Then, a self-sufficient DNA motor autonomously performed the bio-analytical task of imaging miRNA-10b, with a low detection limit of 34 pM. Also, such self-sufficient 3D walkers allowed real-time imaging of MDA-MB-231 cells by intracellular operation. This method demonstrates the self-sufficient 3D DNA motor's bioanalytical application in living cells which may inspire various other biological applications including gene delivery, therapy, etc .